*** RETURN BAHAN AGRO_TOPUP 1 PAGES*** Population dynamics of Aulacophora indica in Felcra Paya Jenuang / Nur Yuhanis Rosli - Rosli, Nur Yuhanis (Faculty of Plantation and Agrotechnology, 2019)
A study on population of Aulacophora indica was done in Felcra Paya Jenuang, Merlimau, Melaka from 25th July 2018 until 14th August 2018. The study aimed to determine the population of Aulacophora indica on different sampling dates and on different traps used. Previous study has shown Aulacophora indica’s preference to the family of Cucurbitaceae as host plant. Yellow pan trap and manual method were used as sampling methods. The yellow pan trap contained soapy water while manual method such as sweeping net was used. Initial assumptions were done in which sampling done in different date was believed to have effect on number of Aulacophora indica collected. It is also believed that usage of yellow pan trap will yield more result as compare to manual method. Interval of 3 days for each sampling method was practiced. This measure was taken to ensure the uniformity of sampling time for both method. Study area was divided into 10 strata of 1 hectare each. 4 strata were used as sampling area. Results for different sampling dates has shown no significant difference while results for different type of traps used has shown a significant difference among them. One-way Anova analysis resulted in (F=0.696, df=5,138 & P>0.01) for different sampling date while unpaired t-test analysis resulted in (F=34.062, df=142,88.728 & P<0.01) for different type of traps used. The study has shown that economic threshold level of Aulocophora indica was not reached. The oil palm trees indicated more than 20% damage due to multiple attack from various insect pest including small number of Aulacophora indica as shown by the mean population thus ruling out their impact on the damage of the plantation area. However, appropriate control methods were suggested to ensure presence of insect pest in the area is under control.